(untitled) - Denis Connor (New Jersey, 1985)
Introduction; Case study description; The basic components of a business information system; Information engineering; Structured analysis and design; Structured requirements definition; Jackson system development; Higher - order software; System prototyping; Application system development methodologies; Data use analysis; The information explosion.
Keywords: Management information systems - Design and construction